An in vitro study of the defluoridating capacity of apog in water samples from Cavite City - Quimpo, Debbie Mae
The study evaluated the use of apog to defluoridate naturally fluoridated water from Cavite City. Three (3) grams of apog was used on eighty (80) ml. of water and the results obtained showed a significant 87% reduction or an average of 0.93 ppm of fluoride removed from the naturally fluoridated water.